IMPLEMENTATION OF INDEPENDENT CURRICULUM, TPACK, AND TEACHER CREATIVITY IN INFLUENCING ECONOMIC LEARNING ACTIVITY - Khotimah, Nurul; Rifda Naufalin, Lina (Jurnal Profesi Keguruan, 2024)
This research is a quantitative study through a survey method that aims to prove that there is an influence on the implementation of the independent curriculum, Technological Pedagogical Content Knowledge (TPACK), and teacher creativity on economic learning activities at SMAN 1 Banyumas. The proportionate stratified random sampling technique was used in this study to take a sample of 207 students. The data analysis technique uses multiple linear regression. The results of research and data analysis that have been carried out show that: (1) There is a positive and significant effect of the implementation of the independent curriculum on students’ learning activeness in economics subjects; (2) There is a positive and significant effect of Technological Pedagogical Content Knowledge (TPACK) on students’ learning activeness in economics subjects; (3) There is a positive and significant effect of teacher creativity on students’ learning activeness in economics subjects.